FAKTOR-FAKTOR YANG MEMENGARUHI AUDIT REPORT LAG - Faiz, Dicky Muhammad; Karmudiandri, Arwina (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
This study aims to find empirical evidence regarding the factors that influence audit report lag. The independent variables in this study are the characteristics of the audit committee, financial conditions, complexity of corporate accounting, auditor reputation, audit tenure, audit opinion, and independent commissioners. This study uses manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2021. The number of samples that were successfully obtained using the purposive sampling method were 131 companies with a total of 393 data. The results of the study show that the characteristics of the audit committee, financial conditions, and independent commissioners have an effect on audit report lag. Meanwhile, the complexity of corporate accounting, auditor reputation, audit tenure, and audit opinion have no effect on audit report lag.